الصياغة الدستورية و أثرها على تفسيرات المحكمة الأتحادية العليا في العراق - ABDULRAHMAN, AVEEN KHALED (Journal of Duhok University, 2020)
The constitutional drafting stage is one of the stages in writing the constitution, which is a process of transferring ideas and principles from their philosophical-intellectual framework to a linguistic framework through a set of expressive words and methods or to make them implement valid, and through fit drafting that able to reach the truth. there are many methods of constitutional drafting, between hard drafting which is specified to the obligation and judgment, and the soft drafting which is not specified that leaves the interpreter for discretionary authority to interpret according to the circumstances and facts, as well as there is ambiguous drafting in which the intention of the legislator cannot be easily known and the fluctuating drafting in which the constitutional drafter handles to fix the same topic, but in different formulations, which leads to ambiguity of the intention of the legislator, and the drafter of the Iraqi constitution in 2005 relied on more than one method in drafting the texts of the constitution, and we show how some of these formulations had a negative impact on the decisions of the Iraqi Federal Supreme Court when exercising its jurisdiction in interpreting the constitution until some of them generated a political and legal controversy at the same time.